Gambaran Dukungan Suami Terhadap Istri yang Menjalani Persalinan di Usia Remaja - Nika Susanti; Wiwin Lismidiati (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2017)
Background: Adolescent pregnancy is a pregnancy that occurs at age under 20 years old. Adolescent pregnancy can cause both physical and psychological complications, especially during labor because adolescent doesn’t have mature reproductive organs. Adolescent facing labor will also experience fear and anxiety. It is necessary to know the role of the husband towards his wife having labor in adolescence age.Objective: This study was aimed to describe the husband support toward wife laboring at the stage of adolescence.Methods: This research was a quantitative descriptive cross-sectional design. As many as 46 husbands were recruited for samples using total sampling method. The instruments used in this study was a questionnaire of husband support in labor modified by the researcher based on literature study results. The data analysis used univariate using descriptive analysis and bivariate analysis using chi-square.Results: In general, the husband’s support given to his wife during labor in adolescence was in the high support category (60,9%). More than 50% of respondents gave emotional, informational, and instrumental support in the high category. Value support has the highest category (73,9%). External factors affecting the husband support were education (p-value = 0,004) and salary (p-value = 0,029).Conclusion: Support given by the husbands is high toward wife laboring at the stage of adolescence is in the high category. ABSTRAK Latar  belakang: Kehamilan  remaja  adalah  kehamilan  yang  terjadi  pada  usia  di  bawah  20  tahun. Kehamilan remaja dapat menimbulkan komplikasi baik fisik maupun psikologis terutama saat persalinan. Remaja  yang  menghadapi  persalinan  juga  akan  mengalami  ketakutan  dan  kecemasan. Untuk  itu  perlu diketahui peran suami pada istri yang menjalani persalinan di usia remaja.Tujuan: penelitian ini bertujuan untuk mengetahui gambaran dukungan suami terhadap istri yang menjalani persalinan diusia remaja.Metode: Penelitian ini merupakan penelitian jenis deskriptif kuantitatif dengan rancangan cross sectional. Sampel dalam penelitian ini sebanyak46 orang suami dengan menggunakan tekniktotal sampling. Alat ukur menggunakan kuesioner dukungan suami dalam persalinan yang telah dimodifikasi peneliti dari hasil studi pustaka. Analisa univariat menggunakan analisis deskriptif, analisis bivariate menggunakan chi-square.Hasil: Dukungan suami secara umum yang diberikan kepada istri saat menjalani persalinan di usia remaja termasuk kategori dukungan tinggi (60,9%). Dukungan penilaian mendapat kategori tinggi terbanyak yaitu sebesar 73,9%, sementara jenis dukungan instrumental paling sedikit (58,71%). Faktor yangberhubungan dengandukungan suami adalah pendidikan (p-value= 0,004) dan penghasilan (p-value = 0,029).Kesimpulan: Dukungan persalinan yang diberikan oleh suami terhadap istri usia remaja termasuk dalam kategori tinggi.